Protocatechuic acid-mediated injectable antioxidant hydrogels facilitate wound healing. (1st February 2023) - Zhou, Chen; Xu, Ruiling; Han, Xiaowen; Tong, Lei; Xiong, Li; Liang, Jie; Sun, Yong; Zhang, Xingdong; Fan, Yujiang
Abstract: Overproduction of free radicals in vivo leads to oxidative stress, which substantially slows the healing of wound. Here, a series of injectable antioxidant hydrogels were designed by protocatechuic acid (PA)-mediated carboxylated chitosan (CCS) composed by conjugating oxidized hyaluronic acid (OHA). These biocompatible OHA/CCS-PA composite hydrogels presented stable chemical structure, physical properties, and effective antibacterial properties against common pathogens exceeding 99%. In addition, OHA/CCS-PA hydrogels demonstrated satisfactory antioxidant capacity to scavenge over 85% of overproduced free radicals, which could reduce the damage of oxidative stress to cellular activity and diminish the expression of reactive oxygen species in vitro by the long-lasting release of phenolic hydroxyl element. More importantly, the results of in vivo animal tests confirmed that OHA/CCS-PA hydrogels could significantly promote wound healing with higher collagen disposition (86.29%) in comparison with commercial Tegaderm™ film and the control hydrogel with physical mixing of PA. These findings indicated that OHA/CCS-PA hydrogel had great potential for wound healing. Graphical abstract: Image 1 Highlights: Antioxidant hydrogels were designed by protocatechuic acid-mediated. Hydrogels presented injectability, antibacterial activity, and biocompatibility. Hydrogels reduced oxidative stress damage by scavenging free radicals in vitro. Hydrogels promoted wound healing and reinforced collagen disposition in vivo.